2013
DOI: 10.1097/nmd.0000000000000061
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Violence During a 4-Week Period in a Psychiatric Outpatient Population

Abstract: The clinical impact of structured risk assessment instruments has been limited by a lack of information regarding a) their short-term accuracy and b) the relationship between change as measured by the instrument and a change in the risk for harm. Data were collected every 4 weeks on a) variables designed to resemble the items of a structured risk assessment instrument, b) substance use, c) social circumstances and mental state, and d) violent behavior. Scores on the variables designed to resemble the items of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“… 7 For cocaine, Buchanan et al identified an increase in violence in psychiatric outpatients related to cocaine specifically. 39 An association in the same direction was not seen here, although the cocaine-using group is more limited in the Swedish setting than in many other countries. 18 …”
Section: Discussionsupporting
confidence: 53%
“… 7 For cocaine, Buchanan et al identified an increase in violence in psychiatric outpatients related to cocaine specifically. 39 An association in the same direction was not seen here, although the cocaine-using group is more limited in the Swedish setting than in many other countries. 18 …”
Section: Discussionsupporting
confidence: 53%
“…When those who were serving a sentence for murder or attempted murder were considered a majority (82.7%) met criteria for dependence/ harmful use of any substance. Other studies have shown that both alcohol 15 and cocaine 16 are associated with violent crime.…”
Section: Discussionmentioning
confidence: 92%
“…When those who were serving a sentence for murder or attempted murder were considered a majority (82.7%) met criteria for dependence/ harmful use of any substance. Other studies have shown that both alcohol 15 and cocaine 16 are associated with violent crime. Among those who were found to have a lifetime substance use disorder, the majority had been introduced to substance use by friends, by spouse or partner.…”
Section: Discussionmentioning
confidence: 92%
“…Lagged prediction models. To test this, three studies used lagged prediction models, which determine if variables measured proximally to violent behavior are more strongly related to outcome, compared to measures from all other assessment periods (Buchanan, Nich, Douglas, Babuscio, & Easton, 2013;Skeem et al, 2006;Yang, Mulvey, Loughran, & Hanusa, 2012). These authors conducted multi--wave assessments of individuals meeting the criteria for psychiatric diagnoses, and identified hostility, alcohol use, and lack of support as proximal indicators of violence.…”
Section: Retrospective Matched Designsmentioning
confidence: 99%